Posted by **JT** on Tuesday, July 13, 2010 at 9:53pm.

Are these complete?

m^2 + 4mn +4n^2 = (m + 2n)(m+2n)

3x^3y^2 – 3x^2y^2 + 3xy^2 =

3xy(x^2y – xy + y)

Thank you

## Answer This Question

## Related Questions

- Simultaneous equation - X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=...
- Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...
- polynomials - I have to simplify (-x^5y^4)^4(3x^2y)^2(1/3xy) I did (x^20y^16)(9x...
- Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...
- Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...
- algebra 2 - (w + 2t)(w^2 - 2wt + 4t^2) (x + y)(x^2 -3xy + 2y^2) =x^3 - 3x^2y + ...
- Math help polynomial - multiply the following polynomial -3x(y^2+2y^2) answer ...
- bobpursly, - Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) ...
- Math! - 1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4? (this ...
- Math - I have no clue how to do this as no values were given and im confused. ...

More Related Questions